The world of Agha Shahid Ali - Ghosh, Tapan Kumar; Chatterjee, Sisir Kumar (Albany : SUNY Press, 2021)
Featuring essays by American, Indian, and British scholars, this collection offers critical appraisals and personal reflections on the life and work of the transnational poet Agha Shahid Ali (1949-2001). Though sometimes identified as an "Indian writer in English," Shahid came to designate himself as a Kashmiri-American writer in exile in the United States, where he lived for the latter half of his life, publishing seven volumes of poetry and teaching at colleges and universities across the country. Locating Shahid in a diasporic space of exile, the volume traces the poet's transnationalist attempts to bridge East and West and his movement toward a true internationalism. In addition to offering close formal analyses of most of Shahid's poems and poetry collections, the contributors also situate him in relation to both Western and subcontinental poetic forms, particularly the ghazal. Many also offer personal anecdotes that convey the milieu in which the poet lived and wrote, as well as his personal preoccupations. The book concludes with the poet's 1997 interview with Suvir Kaul, which appears in print here for the first time.
Front Matter -- Contents -- Preface -- Agha Shahid Ali -- Abbreviations -- Shahid and His Life -- Ghazal for Open Hands -- Shahid, Some Memories -- Somewhere without Me My Life Begins -- Beloved Witness, Beloved Friend -- Agha Shahid Ali -- "Separation's Geography" -- Agha Shahid Ali and the Ghazals in English -- "I will open the waves" -- Out of Focus -- Beginnings -- Braiding Disparate Strands -- Dialing a Joke -- Archiving Absences -- Tradition, Home, and Exile in Agha Shahid Ali's The Beloved Witness -- "It Is This" -- Epistemology of Mourning -- Let Your Mirrored Convexities Multiply -- An Interview with Agha Shahid Ali -- Bibliography -- About the Editors -- About the Contributors -- Index
Online resource; title from digital title page (viewed on March 26, 2021).
JSTOR
Keywords: Agha, Shahid Ali, -- 1949-2001 -- Criticism and interpretation; Agha, Shahid Ali, -- 1949-2001; LITERARY CRITICISM / Poetry; poetry; Criticism, interpretation, etc; Literary criticism; Poetry; Critiques littéraires.; Poésie.